Recent Progress of In‐Depth Analysis Techniques for Si Anodes in Sulfide‐Based All‐Solid‐State Batteries: A Concise Overview and Future Perspective - S. Jayasubramaniyan; Seokjin Kim; Minseok Ko; Jaekyung Sung (ChemElectroChem)
Abstract The utilization of Si anode in sulfide‐based all‐solid‐state batteries (ASSBs) has gained more research attention in recent years to overcome the interface challenges associated with ASSB‐containing Li metal anode. However, the volume expansion feature of the Si, stress/strain evolution inside the electrode, and the parasitic side reaction at the Si/sulfide SE interface are the most predominant limiting factors for practical device applications. It is necessary to investigate and understand the interface challenges through in‐depth analysis in real‐time battery operation to design highly efficient ASSBs for commercial device applications. Hence, this perspective paper provides a summary of the characterization tools and the analysis results related to the Si/sulfide SE interface. Moreover, in this perspective, we emphasize the importance of further investigation of the interface through more advanced in‐depth/operando analysis tools to gain insightful information about the anodic interface, which could be useful for the researchers to design efficient research strategies for solving the challenging issues associated with the anodic interface.